EVALUATION OF SUPERIOR ATHLETES IN INCREASING SOUTH SUMATERA SPORTS ACHIEVEMENTS - Endrawan, Bagus; Rohidi, Tjetjep Rohendi; Sulaiman; Rahayu, Setya (International Journal of Psychosocial Rehabilitation, 2020)
Athlete or athlete is someone who wrestles and actively does training to achieve achievements in the chosen branch. Sports achievements are one of the reflections of a nation, sports achievements can make the name of the nation and the country become fragrant in the world so that the dignity of a nation also increases. This study aims to analyze the context of evaluation coaching featured athletes to increase performance in sports South Sumatra. Evaluation research with descriptive method of qualitative using CIPP design. The population of this study is the athletes who can gold medals in PON 2016 West Java as many as nine athletes and technique sampling using total sampling. Data collection techniques using observation, interviews, and documentation. The results showed that the fostering of the Sriwijaya 2020 flagship program to welcome PON 2020 in Papua was athletes who gained achievements or had control in the 2016 West Java PON namely Athletics, Shooting and Fencing which formed the foundation of the Sriwijaya 2020 flagship program with the encouragement of the government through KONI South Sumatra. The results of the study are useful for recommendations for KONI, South Sumatra Province, Trainers, and Stakeholders to focus more on developing training and training programs.